2017
DOI: 10.1111/cobi.12941
|View full text |Cite
|
Sign up to set email alerts
|

A condition metric for Eucalyptus woodland derived from expert evaluations

Abstract: The evaluation of ecosystem quality is important for land-management and land-use planning.Evaluation is unavoidably subjective, and robust metrics must be based on consensus and the structured use of observations. We devised a transparent and repeatable process for building and testing ecosystem metrics based on expert data. We gathered quantitative evaluation data on the quality of hypothetical grassy woodland sites from experts. We used these data to train a model (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Despite reasonable concerns about the trading among attributes in aggregate scores of biodiversity value or vegetation condition [14], aggregate values are often the metric used to compare gains and losses within biodiversity offsetting. While concepts such as vegetation condition are inherently subjective [29] previous research has demonstrated that experts can generate consistent and reliable aggregate scores that represent biodiversity value and habitat quality [29, 30]. In this paper we consider both individual attributes and an expert generated aggregate index of vegetation condition.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite reasonable concerns about the trading among attributes in aggregate scores of biodiversity value or vegetation condition [14], aggregate values are often the metric used to compare gains and losses within biodiversity offsetting. While concepts such as vegetation condition are inherently subjective [29] previous research has demonstrated that experts can generate consistent and reliable aggregate scores that represent biodiversity value and habitat quality [29, 30]. In this paper we consider both individual attributes and an expert generated aggregate index of vegetation condition.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, we captured expert point predictions about the current and future aggregate condition of a vegetation patch. This approach has been shown to usefully capture complex belief models of existing habitat value [29, 30], though the method has not yet been extended to future predictions. This elicitation exercise was completed by all 29 experts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A desktop structured expert elicitation, with both real and artificial samples, was undertaken within a workshop setting (e.g., Sinclair, Bruce, Griffioen, Dodd, & White, 2018) because it enabled us to: (a) control for variation in species detectability, both among observers and arising from seasonal variation; (b) maximise the range of ecological communities assessed; and (c) reduce cost and logistics. Although experts are often required to undertake assessments in the field, experts also allocate archival plot records to types and review and revise prior allocations based on sample data alone.…”
Section: Workhops and Expert Selectionmentioning
confidence: 99%